1980
DOI: 10.1001/archsurg.1980.01380040093016
|View full text |Cite
|
Sign up to set email alerts
|

Healing of the Perineal Wound

Abstract: This audit has retrospectively assessed the result of primary closure of the perineum irrespective of risk factors for healing: pre-operative radiotherapy, faecal contamination, age, advanced malignancy and diabetes mellitus. 74 consecutive patients (49 males and 25 females median age 70 years) with rectal carcinoma (72) and anal carcinoma (2) who had undergone abdominal perineal excision from August 1989 to December 1999 were identified retrospectively. Complications of the perineal wound were tabulated. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…There is still no universal consensus of opinion about the optimal method of perineal wound management with regard to its closure, drainage and irrigation. Thus, Mazeir et al [18] found no difference in outcome between the primary closure and open packing of the wound in a series of 288 patients and others advocated primary closure and drainage [3,19,20]. Although the wound may have to be packed to control troublesome haemorrhage and in cases of faecal contamination [21] delayed primary closure scored unfavourably in our experience.…”
Section: Discussionmentioning
confidence: 68%
“…There is still no universal consensus of opinion about the optimal method of perineal wound management with regard to its closure, drainage and irrigation. Thus, Mazeir et al [18] found no difference in outcome between the primary closure and open packing of the wound in a series of 288 patients and others advocated primary closure and drainage [3,19,20]. Although the wound may have to be packed to control troublesome haemorrhage and in cases of faecal contamination [21] delayed primary closure scored unfavourably in our experience.…”
Section: Discussionmentioning
confidence: 68%
“…Our frequency of perineal wound dehiscence was similar to that reported by Hay et al 20 The development of a chronic perineal sinus is a serious complication after APR for adenocarcinoma of the lower rectum with a frequency of up to 4 percent at 12 months. [23][24][25][26] In our study, no chronic perineal sinus was observed after sutured perineal omentoplasty with a mean follow-up of 24 months. Perineal hernia after APR is rarely reported in the literature because of the short follow-up periods of most studies.…”
Section: Discussionmentioning
confidence: 90%
“…The surgical technique has not been standardised yet, leading to a controversy in the long-lasting process of establishing such standards. In addition to the discussion whether the peritoneum of the pelvic floor should be sutured or can be left open [1][2][3], there is still an open question how the perineal wound needs to be managed appropriately, either open, half open or even closed [4][5][6][7][8]. Furthermore, it is still unclear and no controlled data are available as to whether a drainage is beneficial and, if yes, what type of drainage is suitable, either a simple drainage or a redon drainage with or without a rinsing device [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%